A comprehensive analysis of WASP-17b's transmission spectrum from space-based observations. Issue 3 (10th March 2022) - Alderson, L; Wakeford, H R; MacDonald, R J; Lewis, N K; May, E M; Grant, D; Sing, D K; Stevenson, K B; Fowler, J; Goyal, J; Batalha, N E; Kataria, T
ABSTRACT: Due to its 1770 K equilibrium temperature, WASP-17b, a 1.99 R Jup, 0.486 M Jup exoplanet, sits at the critical juncture between hot and ultra-hot Jupiters. We present its 0.3–5 $\rm{μ m}$ transmission spectrum, newly obtained with Hubble Space Telescope ( HST ) Wide Field Camera 3 (WFC3) measurements, and, taking advantage of improved analysis techniques, reanalysed HST Space Telescope Imaging Spectrograph and Spitzer Space Telescope Infrared Array Camera observations. We achieve a median precision of 132 ppm, with a mean of 272 ppm across the whole spectrum. We additionally make use of Transiting Exoplanet Survey Satellite (TESS) and ground-based transit observations to refine the orbital period of WASP-17b. To interpret the observed atmosphere, we make use of free and equilibrium chemistry retrievals using the POSEIDON and ATMO retrieval codes, respectively. We detect absorption due to H2 O at >7σ and find evidence of absorption due to CO2 at >3σ. We see no evidence of previously detected Na i and K i absorption. Across an extensive suite of retrieval configurations, we find that the data favour a bimodal solution with high- or low-metallicity modes as a result of poor constraints in the optical and demonstrate the importance of using multiple statistics for model selection. Future JWST GTO observations, combined with the presented transmission spectrum, will enable precise constraints on WASP-17b's atmosphere.